2003
DOI: 10.1081/prg-120016794
|View full text |Cite
|
Sign up to set email alerts
|

Women with Preeclampsia Have Increased Serum Levels of Pregnancy‐Associated Plasma Protein A (PAPP‐A), Inhibin A, Activin A and Soluble E‐selectin

Abstract: Raised levels of PAPP-A in preeclampsia confirm earlier reports. Activin A showed the highest increase over the controls and is thus likely to be a better serum marker for this pathology than the other markers that were tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
82
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 39 publications
(30 reference statements)
14
82
2
Order By: Relevance
“…Such difference in the pattern of circulating levels between the first-and third-trimesters of pregnancy in pregnancies with PE have also been reported for PAPP-A, which is low in the first-trimester but increased at the time of the clinical onset of PE. 8,39,40 Another possible explanation for the differences in our findings from previous reports is the method used IGFBP-3 at 11-13 weeks in preeclampsia S Sifakis et al for measurement of IGFBP-3, which was by enzymelinked immunosorbent assay in our study and by radioimmunoassay in the previous studies. Unlike enzyme-linked immunosorbent assay, the radioimmunoassays do not distinct between the intact and proteolysed forms IGFBP-3 and consequently do not reflect the concentration of IGFBP-3 capable of sequestering IGFs in the bloodstream.…”
Section: Discussioncontrasting
confidence: 66%
“…Such difference in the pattern of circulating levels between the first-and third-trimesters of pregnancy in pregnancies with PE have also been reported for PAPP-A, which is low in the first-trimester but increased at the time of the clinical onset of PE. 8,39,40 Another possible explanation for the differences in our findings from previous reports is the method used IGFBP-3 at 11-13 weeks in preeclampsia S Sifakis et al for measurement of IGFBP-3, which was by enzymelinked immunosorbent assay in our study and by radioimmunoassay in the previous studies. Unlike enzyme-linked immunosorbent assay, the radioimmunoassays do not distinct between the intact and proteolysed forms IGFBP-3 and consequently do not reflect the concentration of IGFBP-3 capable of sequestering IGFs in the bloodstream.…”
Section: Discussioncontrasting
confidence: 66%
“…However, there were no statistical differences in the levels of E-selectin between mild and severe PE (14). In France, Bretelle et al and Bersinger et al in Switzerland reported similar results in increasing Eselectin in PE (15,16). In Carty DM et al study, E-selectin concentrations were higher in women who develop PE in preterm labor lower than 28 weeks (8).…”
Section: Resultssupporting
confidence: 56%
“…Today's World. 2018 Jan; 7 (1): [16][17][18][19] lower in case group (P=0.001). Serum concentration of Eselectin was significantly higher in PE compared to normal pregnant women (78.…”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy-associated plasma protein A (PAPP-A) is a large highly glycosylated protein complex which is synthesized by trophoblasts [28]. It cleaves insulin-like growth factor (IGF) binding proteins, so that free IGF can perform its biological functions.…”
Section: Pregnancy-associated Plasma Protein Amentioning
confidence: 99%